Altered actin isoforms expression and enhanced airway responsiveness in asthma: the crucial role of β-cytoplasmic actin - Alvarez-González, Marisol; Flores-Flores, Angélica; Carbajal-Salinas, Verónica; Bazán-Perkins, Blanca (Frontiers in Physiology, 2025)
Airway hyperresponsiveness, caused by excessive contraction of airway smooth muscle, is a characteristic of asthma involving multiple proteins, including various isoforms of actin and myosin. While α-smooth muscle actin (ACTA2) is linked to hypercontractility, the roles of other isoforms are unclear. Our study investigated the expression of proteins involved in airway smooth muscle contraction and their relation to AHR in an allergic asthma model. Male guinea pigs were sensitized and challenged with ovalbumin, with controls receiving saline. We measured broncho-obstruction and AHR using plethysmography. Protein expression in bronchial and tracheal smooth muscle was analyzed through immunohistochemistry, with proteins identified using electrophoresis and MALDI/TOF-TOF mass spectrometry. In the asthma model, guinea pigs exhibited AHR. The expression of ACTA2, β-cytoplasmic actin (ACTB), and myosin light chains (MYL9) increased, while γ-cytoplasmic actin 1 (ACTG1) was reduced in the bronchial smooth muscle compared to controls. ACTB and ACTA2 expression levels were correlated with AHR, and ACTB was associated with ACTA2, MYL9, and filamin A (FLNA), and inversely with ACTG1. ACTA2 and MYL9 levels showed an inverse association with ACTG1, and the expression levels of FLNA and MYL9 were correlated. Reduced ACTG1 expression was linked to greater AHR. Proteomic analysis confirmed these proteins in guinea pig tracheal smooth muscle, although expression changes differed from the bronchus, except for ACTB, which increased in the asthma model. Our data suggest that increased ACTA2 and ACTB, along with reduced ACTG1, are related to AHR in guinea pigs. MYL9 and FLNA emerge as potential regulators of actin dynamics.